Patient Knowledge Regarding Radiation Exposure From Foot and Ankle Imaging. Issue 4 (August 2020) - Manning, Blaine T.; Bohl, Daniel D.; Idarraga, Alexander J. P.; Holmes, George B.; Lee, Simon; Lin, Johnny L.; Hamid, Kamran S.
Foot and ankle surgeons routinely prescribe diagnostic imaging that exposes patients to potentially harmful ionizing radiation. It is unclear how well patients understand the radiation to which they are exposed. In this study, 946 consecutive new patients were surveyed regarding medical imaging and radiation exposure prior to their first appointment. Respondents compared the amount of radiation associated with chest X-rays (CXRs) with various types of foot and ankle imaging. Results were compared with actual values of radiation exposure from the published literature. Of 946 patients surveyed, 841 (88.9%) participated. Most had private insurance (82.8%) and a bachelor's degree or higher (60.6%). Most believed that foot X-ray, ankle X-ray, "low dose" foot and ankle computed tomography (CT) scan (alluding to cone-beam CT), and traditional foot and ankle CT scan contain similar amounts of ionizing radiation to CXR. This contradicts the published literature that suggests that the actual exposure to patients is 0.006, 0.006, 0.127, and 0.833 CXR equivalents of radiation, respectively. Of patients who had undergone an X-ray, 55.9% thought about the issue of radiation prior to the study, whereas 46.1% of those undergoing a CT scan considered radiation prior to the exam. Similarly, 35.2% and 27.6% reported their doctor having discussed radiation with them prior to obtaining an X-ray and CT scan, respectively. Patients greatly overestimate the radiation exposure associated with plain film X-rays and cone-beam CT scans of the foot and ankle, and may benefit from increased counseling regarding the relatively low radiation exposure associated with these imaging modalities. Level of Evidence: Level III: Prospective questionnaire